Stress analysis of different configurations of 3 implants to support a fixed prosthesis in an edentulous jaw - João Paulo da Silva-Neto; Marcele Jardim Pimentel; Flávio Domingues das Neves; Rafael Leonardo Xediek Consani; Mateus Bertolini Fernandes dos Santos (Sociedade Brasileira de Pesquisa Odontológica, 2014)
This study's aims was to evaluate the stress distribution in a mandibular implant-supported prosthesis and peri-implant bone considering implant quantity, diameter and position using linear 3-D finite element analysis. Models of an anterior jaw comprised 4 groups according to implant quantity, diameter, and position: control group C, 5 regular implants; R, 3 regular implants; W, 3 wide implants; and DTR, 3 regular implants with the distal ones tilted 30º distally. The cantilever was loaded with an axial load of 50 N. Data was evaluated using von Mises stress on implants and maximum principal stress and microstrain on the bone. The W group showed the lowest value of maximum principal stress in peri-implant bone of the loaded side (4.64 MPa) when compared to C (5.27 MPa), DTR (5.94 MPa), and R (11.12 MPa). Lower stress values in the loaded implants were observed in the experimental groups when compared to the C group. However, the unloaded implants presented opposite results. All the screws of the W group presented lower stress values when compared to the C group. However, the R and DTR groups presented an increase in stress values with the exception of the loaded screw. A reduction in the number of implants associated with wider implants reduced the stress in the bone and prosthetic components.